Optimum design of electromechanical vibration isolators - Minnemann Kuhnert, Willian [UNESP]; Cammarano, Andrea; Silveira, Marcos [UNESP]; Paupitz Gonçalves, Paulo José [UNESP] (SAGE Publications, 2020)
Conventional vibration isolators have been used for a long time to isolate a receiver from a source of disturbance. Probably, the most popular example of vibration isolators can be found in automotive suspensions. In vehicles, the spring and damper elements are used to damp road vibration and also to maintain drive handling stability. In this process, the mechanical energy is converted into heat and dissipated in the damper element. The idea of recovering part of the energy has become an attractive topic among researchers over the last three decades. In this context, this study investigates the possibility of replacing the damper element with an electrical circuit coupled to the mechanic system using a permanent magnet/coil transducer. Different electrical circuit configurations are analyzed to study the influence of damping on the mechanical system. Expressions to obtain critical damping and optimum damping to reduce the maximum peak in the frequency response are developed and presented in tabular form for ease of reference. The methodology is then applied to a two-degree-of-freedom system representing a quarter-vehicle suspension model. The results show that coupled electrical circuits can be used to replace fluid dampers in the design of vibration isolators without performance loss.
Keywords: Critical damping; electromechanical; isolator; optimum damping; transmissibility